2013
DOI: 10.2218/ijdc.v8i1.254
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Approach for Data Management Education: A Report from the Data Information Literacy Project

Abstract: This paper describes the initial results from the Data Information Literacy (DIL) project designed to identify the educational needs of graduate students across a variety of science disciplines and respond with effective educational interventions to meet those needs. The DIL project consists of five teams in disparate disciplines from four academic institutions in the United States. The project teams include a data librarian, a subject-specialist or information literacy librarian, and a faculty member represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 10 publications
1
42
0
2
Order By: Relevance
“…The authors of this study also determined that most researchers in this study thought that offering some type of data literacy was required for their students (Carlson et al, 2013). Other studies have also concluded that academic librarians are well positioned to support data literacy and data competencies (Calzada Prado & Marzal, 2013;Gray, 2004;Schield, 2004;Stephenson & Schifter Caravello, 2007).…”
Section: Literature Reviewmentioning
confidence: 76%
See 1 more Smart Citation
“…The authors of this study also determined that most researchers in this study thought that offering some type of data literacy was required for their students (Carlson et al, 2013). Other studies have also concluded that academic librarians are well positioned to support data literacy and data competencies (Calzada Prado & Marzal, 2013;Gray, 2004;Schield, 2004;Stephenson & Schifter Caravello, 2007).…”
Section: Literature Reviewmentioning
confidence: 76%
“…In a study that examined the data information literacy needs of students and the research faculty, Carlson, Johnston, Westra and Nichols (2013) concluded that librarians can leverage teaching opportunities by integrating data into training and that a major "objective of this collaboration was to increase the capacity of librarians to engage with students and faculty" (p. 215). The authors of this study also determined that most researchers in this study thought that offering some type of data literacy was required for their students (Carlson et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The primary goal of the course, titled Research Data Management, was to enable graduate students to acquire foundational knowledge and skills in selected data information literacy (Carlson et al, 2011;Carlson, Johnston, Westra, & Nichols, 2013) that would support long-term habits in planning, management, preservation, and sharing of research data. During the winter term of 2014 the inaugural course had an official enrollment of 11 students, including one faculty member enrolled for credit and two as non-credit auditors.…”
Section: Course Structure Content and Activitiesmentioning
confidence: 99%
“…Understands the advantages of different types of visualization, for example, maps, graphs, animations, or videos, when displaying data" (Carlson et al 2011). In one study, researchers ranked the data visualization competency as being of the highest importance of the 12 competencies (Carlson et al 2013). Libraries likewise prioritize visualization and list it as a desired competency for data librarians in job postings (Lyon et al 2015).…”
Section: Introductionmentioning
confidence: 99%